SOSIALISASI KONSEP PARIWISATA BERKELANJUTAN DALAM PENGELOLAAN OBJEK WISATA PANTAI YEH GANGGA KABUPATEN TABANAN - AGUS MURIAWAN PUTRA (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2009)
ABSTRACT The Bali Sustainable Development Project suggested that the sustainable development concept for Bali should reflect a balance between economy, environment and culture. This should, therefore incorporate the need for continuity of natural resources and production, the need for continuity of culture and the balances within culture, and development as an